Obstacles in Implementing Whiping Punishment for Violators of Islamic Law in Simeulue Regency - Musmulyadi Musmulyadi; Ismaidar Ismaidar; Tamaulina Tamaulina (International Journal of Law, Crime and Justice, 2024)
Aceh Province is the only one in Indonesia that is given the authority to implement Islamic law in all aspects of community life. One aspect that is of concern to the Aceh government is the enforcement of Islamic law. Where, if there is a violation of Islamic law, the perpetrator will be subject to sanctions in the form of ta'zir with a punishment of caning in accordance with the level of his/her guilt after receiving a final verdict from the Aceh Sharia Court. This study uses a qualitative approach with a literature study type of research. In this case, the researcher examines various existing literature related to the implementation of caning punishment, both from books, journals, articles, and even print and electronic media. The results of the literature study show that the implementation of caning punishment in Aceh faces various obstacles in the form of limited budget, human resources, and rejection from many parties who view the implementation of caning punishment as contrary to respect for Human Rights (HAM).